Overuse of Health Care Services in the Management of Cancer: A Systematic Review. Issue 7 (July 2017) - Baxi, Shrujal S.; Kale, Minal; Keyhani, Salomeh; Roman, Benjamin R.; Yang, Annie; Derosa, Antonio P.; Korenstein, Deborah
Abstract : Background: Overuse, the provision of health services for which harms outweigh the benefits, results in suboptimal patient care and may contribute to the rising costs of cancer care. We performed a systematic review of the evidence on overuse in oncology. Methods: We searched Medline, EMBASE, the Cochrane Library, Web of Science, SCOPUS databases, and 2 grey literature sources, for articles published between December 1, 2011 and March 10, 2017. We included publications from December 2011 to evaluate the literature since the inception of the ABIM Foundation's Choosing Wisely initiative in 2012. We included original research articles quantifying overuse of any medical service in patients with a cancer diagnosis when utilizing an acceptable standard to define care appropriateness, excluding studies of cancer screening. One of 4 investigator reviewed titles and abstracts and 2 of 4 reviewed each full-text article and extracted data. Methodology used PRISMA guidelines. Results: We identified 59 articles measuring overuse of 154 services related to imaging, procedures, and therapeutics in cancer management. The majority of studies addressed adult or geriatric patients (98%) and focused on US populations (76%); the most studied services were diagnostic imaging in low-risk prostate and breast cancer. Few studies evaluated active cancer therapeutics or interventions aimed at reducing overuse. Rates of overuse varied widely among services and among studies of the same service. Conclusions: Despite recent attention to overuse in cancer, evidence identifying areas of overuse remains limited. Broader investigation, including assessment of active cancer treatment, is critical for identifying improvement targets to optimize value in cancer care. Abstract : Supplemental Digital Content is available in the text.